Organoleptic Evaluation and Acceptability of Red Bean-Porang Snack Bar as An Alternative Snack for Obesity Adolescents - Herviana, Herviana; Anggraini, Citra Dewi; Solehah, Novia Zuriatun; Rizma, Amalina (Ikatan Sarjana Gizi Indonesia (ISAGI), 2026)
Obesity is one of nutritional problem in adolescents. obesity among adolescents may be associated with the selection of snacks that are high in caloric density. he utilization of local food ingredients, such as red bean flour and porang flour, in the development of snack bars has the potential to provide a healthy alternative snack that supports adolescents’ nutritional needs. The purpose of this study was to develop a snack bar formulated from red bean flour and porang flour as the primary ingredients. The research was conducted on 3 snack bar formulations with varying compositions of red bean flour and porang flour, F1 (95:5), F2 (96:4), and F3 (97:3). Organoleptic and hedonic quality tests were assessed to determine the level of panelists' preference. Testing was conducted on 26 semi-trained panelists. The collected data were analyzed using One-Way ANOVA and Duncan Test for significant results (p<0.05). The results of organoleptic tests on color, aroma, texture, taste and overall the most preferred red bean - porang snack bar were F2 with a color preference value of 4.23, aroma 4.46, texture 3.92, taste 4.26, and overall 4.50. Meanwhile, the hedonic quality test on taste showed no statistical difference (p = 0.920), but the hedonic quality test on texture showed a significant difference (p=0.002). Organoleptic evaluation and acceptability of the red bean-porang snack bar reported that the best formulation was F2, with a proportion of 96g red bean flour and 4g porang flour. This was indicated by the highest scores for each organoleptic aspect.